Role of Endoglin Insertion and rs1800956 Polymorphisms in Intracranial Aneurysm Susceptibility: A Meta-Analysis. Issue 45 (November 2015) - Hu, Xin; Fang, Yuan; Li, Yun-ke; Liu, Wen-ke; Li, Hao; Ma, Lu; You, Chao
Abstract : Abstract: Endoglin is an essential molecule during angiogenesis, vascular development, and integrity. Till now, many studies have investigated the association between endoglin polymorphisms and intracranial aneurysm (IA) risk, with the results remained inconclusive. Therefore, we performed a meta-analysis to summarize the possible association. We searched PubMed and Embase until June 2015 to identify studies addressing the association between endoglin polymorphisms and IA risk. The summary odds ratios (ORs) and their corresponding 95% confidence interval (CI) were calculated to assess the strength of the association. Eleven studies with a total of 1501 cases and 2012 controls were finally included in this meta-analysis, with 10 studies investigating endoglin 6-bp insertion (6bINS) polymorphism and 4 studies investigating 1800956 polymorphism. No significant association between endoglin 6bINS polymorphism and IA risk was detected in overall estimation (I/I vs wt/I + wt/wt: OR = 1.21, 95% CI = 0.87–1.69) or in the subgroup analysis by ethnicity, control source, or ruptured status. However, we observed an association with borderline significance of 6bINS with IA occurrence (I/I vs wt/I + wt/wt: OR = 1.49, 95% CI = 0.99–2.25, P = 0.058) in studies applying matched controls. Furthermore, we detected a significant association for 6bINS polymorphism of endoglin with increased risk of familial IA (I vs wt, OR = 1.64, 95% CI = 1.10–2.42) but not sporadic IA (I vs wt, OR = 1.09, 95% CI = 0.68–1.45). With regard to rs1800956, our pooled results indicated a significantly decreased IA risk in individuals carrying C allele (C/C vs G/C + G/G: OR = 0.65; 95% CI = 0.45–0.94). This meta-analysis provided no evidence for the association between 6bINS polymorphism with overall IA risk. However, we detected a significant association of 6bINS allele with increased risk of familial IA. Also, we found that rs1800956 was significantly related to IA occurrence. Further, well-designed studies with large sample size are warranted and updated meta-analysis is needed to verify our findings.